PROBLEMS OF THE INFORMATION RIGHTS DEVELOPMENT OF A SUBJECT IN CONTEXT OF THE WORLD’S EVENTS ANALYSIS - Коtеrlіn І. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article, the modern tendencies in terms of narrowing of the information rights of a subject are considered. The processes and phenomena that provoke the decrease of rights are analyzed. For instance, the changes in the legislation of the countries that previously put forth the purpose of democracy development and enrichment of the rights and freedoms of a human being are provided as an example, in terms of the recent and major control establishment and limitation in the sphere of information relationships.